Toxicidade do óleo de nim (Azadirachta indica A. JUSS) na espermatogênese de Ceraeochrysa claveru (NAVÁS, 1911)(Neuroptera: Chysopidae): estudo citoquímico, imunocitoquímico e ultraestrutural - Garcia, Ana Silvia Gimenes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The use of organic agriculture is growing due to the awareness of the society about the importance of eating foods free of pesticides and insecticides as harmful to health. Thus, the search for conservation of natural resources is also growing, along with organic agriculture and integrated pest management. In search of insects that can be used in biological control, which is an important tool in organic agriculture and integrated pest management, the lacewings has proved a strong controlling agent, since their larvae are predators of eggs and larvae of many insects pests of different commercial crops. In order to evaluate the effect of neem oil, a plant extract with insecticides properties on lacewings, Diatraea saccharalis eggs were treated with neem oil at three different concentrations and offered as food for the larvae of Ceraeochrysa claveri, thereby evaluating the effect of intake of neem oil on the larval morphology of testis during development of C. claveri, as well as on the process of spermatogenesis of this predator. Histological, ultrastructural, and immunohistochemistry analysis was used to evaluate the toxicity of neem oil on cells of the testis of C. claveri, and this evaluation performed in testes of third instar larvae, pupae and adults. The analyzes showed that the morphology of the testes varies from rounded shape in larvae to elongated shape in pupae and spiral shape in adults, while its color varies from whitish to bright yellow, respectively. The testes are covered by an outer layer and an inner layer, the latter septa emit, which divide the testis into two follicles. The germ cells are grouped into cysts, cystic surrounded by somatic cells. These cysts consist of spermatogonia, spermatocytes, spermatids and spermatozoa. The spermatogonia undergo mitotic division and give rise to spermatocytes, the cells of the cysts are interconnected by ring canals, which allow their synchronous ...

O uso da agricultura orgânica vem crescendo devido à conscientização da sociedade sobre a importância do consumo de alimentos livres de agrotóxicos e inseticidas tão prejudiciais à saúde. Assim, a busca pela preservação dos recursos naturais também está em crescimento, juntamente com a agricultura orgânica e do manejo integrado de pragas. Na busca por insetos que possam ser utilizados no controle biológico, sendo esta uma importante ferramenta na agricultura orgânica e manejo integrado de pragas, os crisopídeos vem se mostrando um forte agente controlador, uma vez que suas larvas são predadoras de diversos ovos e larvas de insetos pragas de diferentes culturas comerciais. Com o propósito de avaliar o efeito do óleo de nim, um extrato vegetal com propriedades bioinseticidas, sobre os crisopídeos, ovos de Diatraea saccharalis foram tratados com óleo de nim em três diferentes concentrações e oferecidos como alimento a larvas de Ceraeochrysa claveri, avaliando deste modo o efeito da ingestão do óleo de nim na fase larval sobre a morfologia do testículo durante o desenvolvimento de C. claveri, assim como sobre o processo de espermatogênese deste predador. Foram utilizadas a análise histológica, ultraestrutural e imunocitoquímica para a avaliação da toxicidade do óleo de nim sobre as células do testículo de C. claveri; sendo esta avaliação realizada em testículos de larvas de terceiro instar, pupas e adultos. As análises demonstraram que a morfologia dos testículos varia de arredondado em larvas, para alongado em pupas e espiralado em adultos, enquanto sua coloração varia de esbranquiçado a amarelo intenso, respectivamente. Os testículos são recobertos por túnica externa e túnica interna, esta última emitindo septos, que dividem o testículo em dois folículos. As células germinativas são agrupadas em cistos, rodeados por células císticas somáticas. Esses cistos são constituidos por ...
Keywords: Nim; Toxicidade - Testes; Insetos como agentes de controle biológico de pragas; Crisopideo; Inseticidas biológicos; Pragas agricolas - Controle integrado; Agricultural pests